A brand-new me! - Winkler, Henry, 1945- (Hank Zipzer, the world's greatest underachiever, 2010)
As he is preparing to attend middle school, Hank, who has learning differences and academic difficulties, gets an unexpected opportunity to audition for a performing arts school where his creativity and humor will be appreciated and nurtured.